The Participatory Governance In Ecotourism Village Development: A Case Study Of Kendan Village - Dafyar Eliadi Hardian; Cut Yasinta; Sarah Ayu Agnestia Pelani; Ferdinand Sahat Parulian Tobing (Publikasi Indonesia, 2025)
This study analyses the forms and strategies of participatory governance in developing Kendan Village as a thematic ecotourism village based on history, culture, and the environment. It employs a descriptive qualitative approach to examine village planning documents and the collaborative practices of local and external actors in supporting community-based tourism development. The results indicate that community participation occurs in various forms, including involvement in village meetings, hospitality training, preservation of local culture, and environmental restoration programs. Strategies for participatory governance are developed through an inter-RW potential zoning approach, enhanced capacity of local human resources, and multi-stakeholder partnerships, which include inter-village collaboration and digital promotion. Despite these promising collaborative initiatives, the management process continues to face challenges such as gaps in community capacity, a lack of established institutions, and limited supporting infrastructure. This study concludes that planned and adaptive participatory governance can be key to successful, sustainable tourism village development. The findings are expected to serve as a conceptual and practical reference for other villages aiming to develop locally-based tourism potential in an inclusive and resilient manner.